Infant illness spanning the antenatal to early neonatal continuum in rural northern Ghana: Local perceptions, beliefs and practices - Engmann, C.; Adongo, P.; Akawire, A.R.; Gupta, M.; Logonia, G.; Affah, G.; Moyer, C.A. (My University, 2013)
Objective:To explore community understanding of perinatal illness in northern Ghana.Study Design:A cross-sectional descriptive study design. Result:253 community members participated in in-depth interviews and focus group discussions, including women with newborn infants, grandmothers and health care providers. Four overarching themes emerged: (1) Local understanding of illness affects treatment practices. Respondents recognized danger signs of illness spanning antenatal to early neonatal periods. Understanding of causation often had a distinctly local flavor, and thus treatment sometimes differed from mainstream recommendations; (2) Mothers are frequently blamed for their infant's illness; (3) Healthcare decisions regarding infant care are often influenced by community members aside from the infant's mother and (4) Confidence in healthcare providers is issue-specific, and many households use a blended approach to meet their health needs. Conclusion:Despite widespread recognition of danger signs and reported intentions to treat ill infants through the formal health care system, traditional approaches to perinatal illness remain common. Interventions need to be aligned with community perceptions if they are to succeed.Journal of Perinatology advance online publication, 24 January 2013; doi:10.1038/jp.2012.151.